THE STUDY OF THE TOPIC «THE ORIGIN AND EVOLUTION OF HUMAN BEING» IN EDUCATIONAL ESTABLISHMENTS - Помогайбо, В.М.; Петрушов, А.В. (World of Medicine and Biology, 2014)
The critical analysis of textbooks and tutorials for comprehensive and higher educational establishments of Ukraine, Russia and English-Speaking countries, in which presented the theme of «The origin and evolution of human being» is maid. It is discovered, that the content of this topic in the Ukrainian textbooks for high schools is obsolete and does not answer modern data of anthropological science and must be updated.